Perancangan dan Implementasi Service Monitoring System (Studi Kasus: PT Z) - Maharani, Herastia; Yonata, Yosi; Manarisip, Indra Henrie (Jurnal Telematika, 2018)
PT Z is a manufacturer company and the sole agent for Y-brand diesel-engine vehicles and its components. PT Z main business consists of vehicle and spare parts sales, and repair services. For the repair services, PT Z provides normal repair service and body repair service. In providing repair services for the customer’s vehicle, the company encounters difficulties in providing the information regarding the status of the customer vehicle that is being repaired at the repair shop. This problem occurred because the service advisor whom responsible to serve customer is not stationed at the repair shop. Thus, when providing the information to the customer, the service advisor needs to check the physical condition of the vehicle in the workshop. In addition, there are difficulties for the repair shop in monitoring the status of each workstation in the workshop which is a place for repairing customer vehicle. Monitoring is required so that if there is any issue on a workstation, the company can immediately take action to solve these issues so it will not hinder the repair process. The system designed to assist the integration between the service advisor, the workshop, and the head of the workshop as the party responsible for all activities in the workshop. The head of the workshop is responsible for monitoring every customer service vehicle status and workstation status in the workshop. The system designed can also help the customer to be able to monitor directly the status of the vehicle being in-service at the workshop without having to contact the service advisor. Besides that, the system designed can also provide reports related to the number of repairs performed in the company in a month, either the normal service or the body repair service. Based on User Acceptance Test that has been done, repair monitoring system for service advisor has Performance Expectancy value of 85%, workshop head has 90% Performance Expectancy, and for the customer has Performance Expectancy value of 88%. PT Z adalah produsen dan agen tunggal dari kendaraan bermesin diesel bermerk Y beserta komponennya. PT Z bergerak di bidang penjualan mobil dan suku cadang, serta service kendaraan. Untuk layanan service kendaraan, PT Z menyediakan jasa service normal dan body repair. Dalam melakukan pelayanan service kendaraan customer, perusahaan mengalami kesulitan ketika harus memberikan informasi terkait status kendaraan customer yang sedang diperbaiki di bengkel perusahaan. Hal ini dikarenakan bagian service advisory yang bertugas untuk melayani customer tidak berada di bengkel, sehingga ketika akan memberikan informasi kepada customer maka bagian service advisor harus melakukan pengecekan kondisi fisik kendaraan customer. Selain itu terdapat kesulitan bagi perusahaan dalam melakukan pemantauan terhadap status dari setiap workstation yang ada di bengkel yang menjadi tempat perbaikan kendaraan customer. Pemantauan diperlukan agar ketika terjadi kendala pada workstation maka pihak perusahaan dapat langsung mengambil tindakan untuk mengatasi kendala tersebut sehingga tidak akan menghambat proses service kendaraan customer. Sistem yang dirancang membantu adanya integrasi diantara service advisor, bagian bengkel, dan juga kepala bengkel sebagai pihak yang bertanggung jawab terhadap seluruh kegiatan yang ada di bengkel. Kepala bengkel bertanggung jawab dalam melakukan pemantauan terhadap setiap status service kendaraan customer dan status workstation yang ada di bengkel. Sistem yang dirancang juga dapat membantu pihak customer untuk dapat melakukan pemantauan secara langsung terhadap status kendaraannya yang sedang di-service dibengkel tanpa harus menghubungi bagian service advisory. Selain itu sistem yang dirancang juga dapat memberikan laporan terkait jumlah service yang ada di perusahaan dalam sebulan baik service normal atau service body repair. Berdasarkan User Acceptance Test yang dilakukan, sistem monitoring service untuk bagian service advisory memiliki nilai performance expectancy sebesar 85%, bagian kepala bengkel memiliki nilai performance expectancy sebesar 90%, dan bagi customer memiliki nilai performance expectancy sebesar 88%.